2013
DOI: 10.1097/opx.0000000000000002
|View full text |Cite
|
Sign up to set email alerts
|

Monovision Surgery in Myopic Presbyopes

Abstract: Monovision excimer laser correction provides both effective and satisfactory results and should be considered as an option for individuals with myopic presbyopia suitable for, and interested in, refractive surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 12 publications
0
21
0
4
Order By: Relevance
“… 4 Monovision with LASIK has been shown to be a safe and effective means of treating presbyopia with high patient satisfaction. 5 7 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 4 Monovision with LASIK has been shown to be a safe and effective means of treating presbyopia with high patient satisfaction. 5 7 …”
Section: Introductionmentioning
confidence: 99%
“…A few studies have been performed regarding the use of LASIK monovision in emmetropes; however, they indicate promising results with regard to effectiveness and patient satisfaction. 3 , 7 9 In this study, we assess the visual and patient-reported outcomes of emmetropic patients who underwent LASIK specifically for monovision to treat presbyopia.…”
Section: Introductionmentioning
confidence: 99%
“…Larger clinical trials are mandatory to confirm the long-term safety and effectiveness of trifocals and extended depth of focus IOLs. [ 5 45 46 47 ]…”
Section: Discussionmentioning
confidence: 99%
“…Induction of monovision using laser vision correction (LVC) is the simplest approach to laser presbyopia correction; it has a 90% success rate, although there are disadvantages, including reduced visual acuity in darkness, loss of contrast sensitivity, reduction of stereopsis, and intermediate vision reduction. [ 4 5 ]…”
Section: Corneal Presbyopia Surgerymentioning
confidence: 99%
“… 1 3 Change in stereoacuity has previously been investigated for treatments of presbyopia, such as monovision laser in situ keratomileusis (LASIK) and monovision contact lenses. 4 , 5 However, in this work, we compare the stereoacuity of patients before and after KAMRA inlay implantation.…”
Section: Introductionmentioning
confidence: 99%